Effectiveness Of Cirebon City Regional Regulation No. 4 Year 2013 On Violations Of The Distribution And Sale Of Alcoholic Beverages In Cirebon City - Yudha, Yodie Pratama; Fathurahman, Farhan Ahmad; Hayati, Nur; Harmono, Harmono; Gunawan, Moh Sigit (Equivalent: Jurnal Ilmiah Sosial Teknik, 2024)
The objectives of this study are: a) To determine the effectiveness of Cirebon City Regional Regulation No. 4 of 2013 concerning the prohibition of the circulation and sale of alcoholic beverages in Cirebon City; b) To investigate the efforts of the Cirebon City government in tackling the circulation of liquor following the issuance of the Regulation of the Minister of Trade No. 20/M-DAG/PER/4/2014. This study uses a qualitative method. The population includes the Cirebon City Government and the Cirebon City DKUKMPP Office, where alcoholic beverages are sold. The sampling technique used allows the researcher to select information sources based on their relevance and ability to provide necessary data. The data analysis is conducted qualitatively, involving the following steps: 1) Completing any missing data to ensure it is comprehensive and accurate; 2) Reducing and summarizing collected data to focus on key points, which are then systematically organized. The research findings indicate that the circulation of alcoholic beverages in Cirebon City has many adverse effects and negatively influences its development as a City of Guardians. This prompted the local government to prohibit liquor circulation. However, the enforcement of this prohibition has been hindered by the issuance of the Minister of Trade Regulation No. 20/M-DAG/PER/4/2014, complicating efforts by Satpol PP to regulate liquor in certain areas of Cirebon City.